2016
DOI: 10.15376/biores.11.3.6489-6504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Mechanical Properties of Sawdust-High Density Polyethylene Composites under Various Strain Rates

Abstract: There is a need to understand the effect of wood particle size, as it affects the characteristics of wood-based composites. This study considers the effect of wood particle size relative to the dynamic behavior of wood composites. The compression Split Hopkinson Pressure Bar (SHPB) was introduced to execute dynamic compression testing at the strain rate of 650 s , whereas a conventional universal testing machine (UTM) was used to perform static compression testing at the strain rate of 0.1 s , and 0.001 s -1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…Obviously, for a fixed volume of brakepad matrix the sample with higher particle size, hence higher pores sizes and distribution will exhibit less mass, and hence less density which corroborates the model result. This explains the results earlier obtained by Dagwa et al [2], Yawas et al [4], Zykova et al [9], Ameh et al [10] and Jaya et al [6].…”
Section: = + ½supporting
confidence: 81%
See 2 more Smart Citations
“…Obviously, for a fixed volume of brakepad matrix the sample with higher particle size, hence higher pores sizes and distribution will exhibit less mass, and hence less density which corroborates the model result. This explains the results earlier obtained by Dagwa et al [2], Yawas et al [4], Zykova et al [9], Ameh et al [10] and Jaya et al [6].…”
Section: = + ½supporting
confidence: 81%
“…During braking, the brakes are exposed to continuous compressive force and the result show that the 90µm sample will do well under such conditions. The observed trend in the relationship between compressive strength and grain size is corroborated by the conclusions of Yawas et al [4] and Jaya et al [6].…”
Section: Ss-based Brakepad Particle Grain Size Msupporting
confidence: 81%
See 1 more Smart Citation
“…Compressive strength, at different filler weight contents and strain rates of PP/S, [112] PP/ZnO, [57] E/S, [113] E/ GO, [114] E/CNT, [115] PE/GNP, [116] PE/C, [117] E/PS, [118] and PE/SD. [119] C, clay; E, epoxy; GO, graphene oxide; GNP, graphene nanoplatelets; PE, polyethylene; PP, polypropylene; PS, polystyrene microspheres; S, silica; SD, sawdust; ZnO, zinc oxide F I G U R E 1 4 Compressive modulus (measured at a strain rate of 10 3 s À1 ), at different filler weight content of PP/S, [112] PP/ ZnO, [57] E/GO, [114] PE/C, [117] E/PS, [118] and PE/SD, [119] and E/GNP. [120] C, clay; E, epoxy; GO, graphene oxide; GNP, graphene nanoplatelets; PE, polyethylene; PP, polypropylene; PS, polystyrene microspheres; S, silica; SD, sawdust; ZnO, zinc oxide the strength of the particle-matrix interfacial bonding strength is more important than the quality of the particle dispersion, in terms of an enhancement in mechanical properties.…”
Section: Dynamic Mechanical Performance Of Composites 41 | Polymers Filled With Particlesmentioning
confidence: 99%
“…Astari et al showed that the physical and mechanical properties of wood-waste particleboard depend on the size of the particle [19]. Other studies found that the mechanical property of composite may depend on particle sizes [20][21][22]. The previous work of rice straw epoxy resin composite was only studied for 20 mesh particle size of the rice straw [16].…”
Section: Introductionmentioning
confidence: 99%